Synthesis, characterization, and thermal stability of homopolymer and copolymer of some 3-aryl-2-hydroxypropyl methacrylates - Coskun, M; Demirelli, K; Ersöz, M (Marcel Dekker Inc, 2002)
Three new hydroxypropyl methacrylates having three different aryl rings were synthesized by addition of 2,3-epoxypropyl aromatic hydrocarbon to methacrylic acid. The monomers prepared are 3-phenyl-2-hydroxypropyl methacrylate, 3-tolyl-2-hydroxypropyl methacrylate, (THPMA), and 3-naphtyl-2-hydroxypropyl methacrylate. The homopolymers of these monomers and two different copolymers, [poly(THPMA-co-BMA)], were obtained from polymerization at 60degreesC in 1,4-dioxane solution using AIBN as initiator. All the monomers and the polymers were characterized by FT-IR and H-1 and C-13 NMR techniques. Solubility parameters of the polymers and average molecular weight of poly(THPMA) were determined. Thermal stabilities of the polymers were given as comparing with each other by using TGA curves. Thermal degradation of poly(THPMA60%-co-BMA40%) was studied in detail.
Keywords: synthesis; 2-hydroxypropyl methacrylate; thermal stability